August: Osage County [videorecording (DVD)] - Streep, Meryl; Roberts, Julia, 1967-; McGregor, Ewan, 1971-; Cooper, Chris, 1951-; Breslin, Abigail, 1996-; Lewis, Juliette; Cumberbatch, Benedict, 1976-; Martindale, Margo, 1951-; Mulroney, Dermot; Nicholson, Julianne, 1971-; Upham, Misty, 1982-2014; Shepard, Sam, 1943-2017 (2013)
The dark, hilarious, and deeply touching story of the strong-willed women of the Weston family, whose lives have diverged until a family crisis brings them back to the Midwest house they grew up in, and to the dysfunctional woman who raised them.